Recommendation System for Selecting Electronic Products Using Content-Based Filtering Method - Exzaraja Indiandra Scandea; Susanto, Rudi; Muhtarom, Moh (Jurnal Inotera, 2024)
This study aims to develop a recommendation system for electronic products using the Content-Based Filtering method. In this research, calculations were performed to identify 12 products that exhibit similarity based on their respective categories. The method employed for these calculations was cosine similarity, which measures the degree of similarity between products. The analysis results indicate that there are three products with the highest similarity values, specifically 73, 71.15, and 64.89. These products were selected based on their relevant characteristic similarities and features, thereby providing accurate recommendations for consumers. This recommendation system is expected to significantly enhance the online shopping experience by assisting consumers in finding products that align closely with their preferences and needs. Consequently, this research offers substantial contributions to companies seeking to improve customer satisfaction and operational efficiency, ultimately leading to better consumer engagement and increased sales in the competitive electronic market.